Systematic review of microRNAs in human acute kidney injury - Adrianna Douvris; Jose L. Viñas; Shareef Akbari; Karishma Tailor; Manoj M. Lalu; Dylan Burger; Kevin D. Burns (Renal Failure)
Introduction Early diagnosis of acute kidney injury (AKI) is limited with current tools. MicroRNAs (miRNAs) are implicated in AKI pathogenesis in preclinical models, but less is known about their role in humans. We conducted a systematic review to identify dysregulated miRNAs in humans with AKI.Methods We searched Ovid MEDLINE, Embase, Web of Science, and CENTRAL (August 21, 2023) for studies of human subjects with AKI. We excluded reviews and pre-clinical studies without human data. The primary outcome was dysregulated miRNAs in AKI. Two reviewers screened abstracts, reviewed full texts, performed data extraction and quality assessment (Newcastle Ottawa Scale).Results We screened 2,456 reports and included 92 for synthesis without meta-analysis. All studies except one were observational. Studies were grouped by etiology of AKI: cardiac surgery-associated (CS-AKI, n = 13 studies), sepsis (n = 25), nephrotoxic (n = 9), kidney transplant (n = 26), and other causes (n = 19). In total, 128 miRNAs were identified to be dysregulated across AKI studies (45 miRNAs upregulated, 55 downregulated, 28 both). miR-21 was the most frequently reported (n = 17 studies) and it was increased in all etiologies except CS-AKI where it was decreased (n = 3 studies). Study limitations included bias due to targeted approaches, absence of clinical data/controls, and miRNA normalization methods. Overall study quality was fair (median 5/9, range 2-8 points).Conclusion Dysregulated miRNAs, particularly miR-21, have potential as AKI biomarkers. These results should be interpreted cautiously due to methodological limitations. Standardized methods and unbiased approaches are needed to validate candidate miRNA biomarkers.Registration: International Prospective Register of Systematic Reviews (PROSPERO CRD42020201253)